Web-based video for real-time monitoring of radiological procedures. - Ratib, O. (IEEE Transactions on information technology in biomedicine)
Web-based video transmission of images from CT and MRI consoles is implemented in an intranet environment for real-time monitoring of ongoing procedures. Images captured from the consoles are compressed to video resolution and then broadcast through a Web server. When called upon, the attending radiologists can view these live images on any computer within the secured intranet network. With adequate compression, these images can be displayed simultaneously in different locations at a rate of 2 to 5 images/s through a standard local area network. While the quality of the images was insufficient for diagnostic purposes, our user survey showed that they were suitable for supervising a procedure, for positioning the imaging slices, and for routine quality checking before completion of a study. The system was implemented at UCLA to monitor nine CTs and six MRIs distributed in four different buildings. This system significantly improved the radiologists' productivity by saving valuable time spent in trips between reading rooms and examination rooms. It also improved patient care and throughput by reducing the time spent waiting for the radiologists to check a study before removing the patient from the scanner.